On My Father's Wings an entrepreneurial journey of finding humility, resiliency and a lasting legacy - Shirima, Michael (River Grove Books, 2022)
Michael Shirima is an exceptional figure whose perseverance and stalwart principles of faith, family and friends contributed to his astounding and inspirational career navigating the inherent challenges and obstacles of the air transport industry in Africa.
Keywords: Biography